Recent Trends in Nanomaterials Synthesis and Properties - Khan, Zishan Husain; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book focuses on the latest advances in the field of nanomaterials synthesis and processes, and provides a comprehensive overview of the state-of-the-art research in this rapidly developing field. The book is divided into 11 chapters on various aspects of nanomaterials, moving from the synthesis and characterization of graphene oxide to graphene quantum dots and other interesting nanomaterials. Some chapters based on theoretical simulation of nanomaterials and their properties and applications of nanomaterials are also presented in this book. Given the depth and breadth of coverage, the book offers a valuable guide for researchers and students working in the area of nanomaterials.
Synthesis and Characterization of Graphene Oxide -- Carbon Nanomaterials Derived from Graphene and Graphene Oxide Nanosheets -- Synthesis, Characterization, and Applications of Graphene Quantum Dots -- Surface Modified ZnO for Sunlight Photocatalytic Decontamination of Water -- Wear Behavior of Composites and Nanocomposites: A New Approach -- Facile Synthesis of Large Surface Area Graphene and its Applications -- Prospects of Nanostructured Zirconia as a Point-of Care Diagnostics -- Introduction to Nano-Biosensors -- Synthesis and Characterization of Methyl Ammonium Lead Iodide for Perovskite Solar Cells -- Carbon Nanowalls: A Potential 2-Dimensional Material for Field Emission and Energy Related Applications -- Laser Assisted Molecular Beam Epitaxy of Gan Nanowall Networks: Growth and Physical Properties -- Density Functional Theory (DFT) Study of Novel 2D and 3D Materials.
Keywords: Nanotechnology; Microtechnology; Microelectromechanical systems; Nanoscience; Nanotechnology; Microsystems and MEMS; Nanophysics